Laboratory investigation of a load carriage task observed in forestry - Furney, Sheena Elizabeth (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2007)
The objective of the present study was to investigate and compare the human responses to two load carriage tasks performed with three different load masses and on three different gradients. The task of carrying hydrogel in one hand was observed in a silviculture industry and crude physiological and perceptual responses were measured. This task was simulated in a laboratory setting together with a suggested intervention of backpack carriage. Eighteen conditions were established which consisted of the two modes of carriage and a combination of three load masses (9kg, 12kg and 15kg) and three gradients (5%, 10% and 15%). Twenty eight Rhodes University female students comprised the sample and the experimental procedures were conducted on a Quinton treadmill. Each participant was required to complete nine of the eighteen conditions which were each four minutes in duration. Postural changes were assessed using lateral and posterior digital images taken at the second and fourth minute and compression and shearing forces were estimated with the ErgolmagerTM Physiological responses (heart rate, ventilation and metabolic responses) were measured continuously with the Quark bÂ² and perceptual responses ('central' and 'local' RPE) were measured every minute during the experimentation and body discomfort was rated at the completion of each condition. Overall responses revealed that hand carriage (146 bt.minâ »Â¹ , 25.09 mIOâ‚‚. kg-l.minâ »Â¹) was generally found to be more physiologically stressful than backpack carriage (130 bt.minâ »Â¹, 22.15 mIOâ‚‚.kgâ »Â¹ .minâ »Â¹) independent of load mass and gradient. Physiological responses were higher (113 bt.min-1 to 174 bt.minâ »Â¹ ) in responses to increasing gradient as opposed to increasing load mass (104 bt.min-1 to 153 bt.minâ »Â¹ ) for both backpack and hand carriage. Categorisation using the guidelines of Sanders and McCormick (1993) allowed for classification of conditions, with respect to physiological responses, into 'moderate', 'heavy' and 'very heavy' stress. For almost all of the physiological responses the majority of conditions which were classified as 'moderate' were backpack carriage conditions and the conditions classified as 'very heavy' were mostly hand carriage conditions. In terms of postural responses hand carriage resulted in more strain and greater compression and shearing forces on the spine. In terms of the compression forces increasing gradient had a greater affect on backpack carriage (681 N to 935 N) compared to hand carriage (570N to 793N). In contrast, increasing load mass had a larger affect on hand carriage postures and compression forces (751 N to 935N) in comparison to backpack carriage (723N to 780N). Shearing forces were found to be worse in hand carriage conditions overall. Although participants generally underrated perceived exertion in relation to cardiorespiratory responses, these perceptions revealed that backpack carriage, with a mean 'central' RPE of 12 compared to 11 for hand carriage, was somewhat preferred to hand carriage and that increasing gradient was perceived to be marginally more straining than increasing load mass.
Keywords: Work -- Physiological aspects; Foresters -- Workload; Human engineering; Lifting and carrying